THE ORDER OF ENTIRE FUNCTIONS OF BOUNDED INDEX IN DIRECTION - Bandura, Andriy Ivanovych; Kulinich, Halyna Mykhailivna; Shegda, Liubov Mykhailivna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Estimates of order of entire solutions for partial differential equations are obtained. These solutions are functions of bounded index in direction.